Knowledge and Practice of Asthmatic Children's Parents About Daily Air Quality - Yazdanparast, Taraneh (National Research Institute of Tuberculosis and Lung Disease, 2013)
BACKGROUND: Knowledge and practice about air pollution are essential subjects in special groups such as cardio-pulmonary patients. For children with air pollution-related diseases, knowledge and attitude of parents play a determining role in this respect. Since providing a coherent curriculum needs evidence-based information, this survey was conducted to assess the knowledge and practice of asthmatic children's parents about daily air quality since asthmatic children are among the most vulnerable at-risk groups when it comes to air pollution. MATERIALS AND METHODS: All parents of asthmatic children referred to the Pediatric Clinic of Masih Daneshvari Hospital during one year period (250 people) completed knowledge and practice questionnaire on air pollution. Knowledge questions consisted of familiarity with pollution standard index (PSI), ways to find out about it, respiratory effects of air pollution and etc. Practice questions consisted of reducing outdoor presence and activity of children and actions taken to reduce air pollution in polluted days. RESULTS: In general, 3.2% of parents were familiar with PSI, 12.5% were aware of ways to find out about daily air quality, 65.2% were aware of air pollution respiratory effects, 65.6% were aware of air pollution effects on asthmatic children and 4.4% were aware of ineffectiveness of surgical masks in prevention of air pollution health effects. The obtained practice score ranged from 4 to 16, and the participants’ mean score was equal to 11.79. CONCLUSION: This study revealed that parents of asthmatic children were aware of air pollution hazards for their children and wanted to prevent them but they did not know how. Therefore, asthmatic children in Tehran are still exposed to risks of air pollution.